A Meta-Analysis of the Relationship between Intrinsic Religiosity and Locus of Control. (September 2013) - Coursey, Lauren E.; Kenworthy, Jared B.; Jones, Jennifer R.
The authors meta-analytically examined the relationship between intrinsic religiosity and internal locus of control. Thirty-seven independent samples, comprising 9, 924 participants, yielded an average effect size of r = .06, which was small, but significant, indicating a positive correlation between intrinsic religiosity and internal locus of control. Moderation analyses showed a significant trend of effects becoming weaker over time (from 1971 to 2011). The judged religiousness of samples significantly predicted the strength of the correlation, such that more religious samples showed stronger effect sizes.